Identification of Determinants and Implementation Strategies to Increase PrEP Uptake Among Black Same Gender–Loving Men in Mecklenburg County, North Carolina: The PrEP-MECK Study. (1st July 2022) - Corneli, Amy; Perry, Brian; Wilson, Johnny; Reif, Susan; Gulden, Chelsea; Hanlen-Rosado, Emily; Cooper, Haley; Taylor, Jamilah; Starling, Summer; Thompson, J. Wesley
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Pre-exposure prophylaxis (PrEP) use is low among Black same gender–loving men (BSGLM) in Mecklenburg County, NC, an Ending the HIV Epidemic priority jurisdiction. We created PrEP-MECK—an investigator partnership among a community-based organization representative, a PrEP provider, and researchers—and conducted iterative preparation research to identify determinants of PrEP uptake and implementation strategies to address them. Methods: We first established the PrEP-MECK Coalition of community stakeholders. Next, informed by PrEP-MECK Coalition input and PRECEDE-PROCEED's educational/ecological assessment phase, we conducted focus group discussions with BSGLM not using PrEP and in-depth interviews with BSGLM who were currently or had previously taken PrEP to describe determinants and suggest implementation strategies. Based on interim findings, we partnered with clinics participating in the Mecklenburg County PrEP Initiative, which offers free PrEP services to uninsured individuals. We also conducted Consolidated Framework for Implementation Research–informed organizational assessments with community-based organizations and clinics to assess readiness to pilot the implementation strategies. Results: We conducted 4 focus group discussions, 17 in-depth interviews, and 6 assessments. BSGLM were aware of PrEP yet perceived that costs made it unattainable. Awareness of how to access PrEP and the Mecklenburg County PrEP Initiative was lacking, and clinic scheduling barriers and provider mistrust limited access. We identified client-level implementation strategies, primarily focusing on engaging the consumer, to increase comfort with and awareness of how to access PrEP, and clinic-level implementation strategies focusing on changing clinic infrastructure, to make PrEP access easier. Conclusion: We plan to evaluate implementation of these strategies once fully developed to determine their acceptability and other outcomes in future research.